Forensic accounting as a mechanism for controlling and detecting financial fraud - Jarallah, Meaad Nasser; Alsayed, Huda Ebrahim (Journal of Economic, Administrative and Legal Sciences, 2022)
This research aims to clarify the role of forensic accounting in controlling and discovering financial fraud practices considering that Forensic accounting is one of the mechanisms that helps controlling and discovering financial fraud. The research aims to explore the extent of availability of the required organizational and legislative environments for forensic accountability implementation when settling the disputes of financial nature in a fair manner. The researcher adopted a descriptive analytical approach. We designed a questionnaire from 26 paragraphs as a tool to collect data and distributing it to a sample of 150 respondents. We use SPSS statistical analysis program to analyze our sample. Our results show that, forensic accounting helps us to understand how to review financial statements for fraud indicators and support the knowledge of financial and accounting issues.
Keywords: forensic accounting; financial fraud; forensic accounting mechanisms